EFEKTIVITAS PROMOSI PEMASARAN TERHADAP MINAT BELI BOTOL LITERAN DUA COFFEE (STUDI KUANTITATIF BOTOL LITERAN DUA COFFEE) - Peter Adam Baldwin (2022)
This study aims to determine how big is the effectiveness of marketing promotions on the interest of buying bottle litre from Dua Coffee. With using the theory of consumer behavior and supported by the theory of mass communication effects. The method that being used is comparative quantitative by using the primary data sources and the secondary data. The sampling technique was done by using the simple random sampling. The research uses the Slovin formula to generate the answers from the data obtained with the help of the SPSS. Based on the problem, hypothesis and research results. It can be concluded that there is a positive and significant influence on the research entitled "The Effectiveness Of Marketing Promotions On The Interest Of Buying Bottle Litre From Dua Coffee". Based on the data that has been collected and the tests that have been carried out with the t test using a significance value with a confidence level of 95% , the following conclusions can be drawn: From the results of testing the research hypothesis, there is a positive influence and a positive correlation between the effectiveness of marketing promotions for bottle litre Dua Coffee and the purchasing decisions from customer for bottle litre Dua Coffee. That means, the better the marketing promotion for the bottle litre Dua Coffee will mak more consumers purchase it. This is the evidence by the value of the t test results which value the variable x public relations shows that t Count 2,815 > t Table 0,677. Dua Coffee itself also carries out quite high marketing promotion activities, especially for health workers in this era of the Covid-19 pandemic so that public relationns gets the highest score in the t test. So it can be stated that the hypothesis H1 which states " there is an effect of the effectiveness of marketing promotions on buying interest in bottle litres Dua Coffee" is accepted based on the assumptions of the previous hypothesis. Keywords: Marketing promotion, correlation, bottle litre, purchasing decisions, consumers